Prevalence, patterns and determinants of tobacco and alcohol use among construction site workers in Dehradun, Uttarakhand - Upadhyai, Neha; Gupta, Kajal; Mittal, Amit (Indian Journal of Community Health, 2025)
Background: The construction industry is a vast industry in India, employing millions of workers. Higher rates of tobacco and alcohol use is seen among its workers. Aims and Objectives: The objective of the study was to determine the prevalence, patterns and determinants of tobacco and alcohol use among them. Methodology: A Cross-sectional study was conducted at a construction site on 401 study participants, using a pre-designed and pre-tested schedule. Socio demographic and other data about tobacco and alcohol use were taken from them. The data was analyzed by using Chi-square test of significance for testing the associations of various variables with tobacco and alcohol use. Results: Prevalence of tobacco use was 73% and alcohol was 38.4%. Age, gender, marital status and education were found to be significantly associated with both tobacco and alcohol use. Conclusion: The high prevalence of tobacco and alcohol use by the workers warrants strong measures so that they remain healthy and tobacco free.